1993
DOI: 10.1007/bf00357103
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome length and DNA loop size during early embryonic development of Xenopus laevis

Abstract: The looped organization of the eukaryotic genome mediated by a skeletal framework of non-histone proteins is conserved throughout the cell cycle. The radial loop/scaffold model envisages that the higher order architecture of metaphase chromosomes relies on an axial structure around which looped DNA domains are radially arranged through stable attachment sites. In this light we investigated the relationship between the looped organization and overall morphology of chromosomes. In developing Xenopus laevis embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 40 publications
4
30
0
Order By: Relevance
“…Given the fixed volume of a chromatin fiber whose density within a chromosome has been shown to be constant from prometaphase through metaphase (Mora-Bermudez et al 2007), axial shortening would create shorter and thicker chromatids, whereas lateral compaction would make chromatids longer and thinner. In fact, it has been demonstrated that chromosomes progressively get shorter and thicker during animal development (Belmont et al 1987;Micheli et al 1993). On the basis of the ratio manipulation experiments reported here, we propose that the primary actions of condensin I and II are aimed at lateral compaction and axial shortening, respectively, and that their intricate balance acts as one of the critical determinants in shaping chromatids (Fig.…”
Section: Conclusion and Perspectivesupporting
confidence: 53%
See 2 more Smart Citations
“…Given the fixed volume of a chromatin fiber whose density within a chromosome has been shown to be constant from prometaphase through metaphase (Mora-Bermudez et al 2007), axial shortening would create shorter and thicker chromatids, whereas lateral compaction would make chromatids longer and thinner. In fact, it has been demonstrated that chromosomes progressively get shorter and thicker during animal development (Belmont et al 1987;Micheli et al 1993). On the basis of the ratio manipulation experiments reported here, we propose that the primary actions of condensin I and II are aimed at lateral compaction and axial shortening, respectively, and that their intricate balance acts as one of the critical determinants in shaping chromatids (Fig.…”
Section: Conclusion and Perspectivesupporting
confidence: 53%
“…It is known that metaphase chromosomes in early embryonic cells tend to be longer and thinner compared with those in somatic cells (Belmont et al 1987;Micheli et al 1993), and the chromosomes assembled in Xenopus egg extracts recapitulate the embryonic properties (Fig. 1B,C).…”
Section: The Relative Ratio Of Condensin I To Ii Is a Critical Determmentioning
confidence: 79%
See 1 more Smart Citation
“…The condensin I to condensin II ratio in egg extracts is about 5:1, while in somatic HeLa cells it is closer to 1:1 (Ono et al 2003). It has been documented that metaphase chromosomes in Xenopus embryos are twice as long as and substantially narrower than those in swimming larvae (Micheli et al 1993), the difference in condensation perhaps being due to different ratios of condensin I and II or to cohesin domain or replicon size (Marilley & Gassend-Bonnet 1989).…”
Section: Stretching and Bending Elasticitymentioning
confidence: 99%
“…In Xenopus, shortening and thickening of metaphase chromosomes from the blastula to the swimming larva stages is accompanied by a signi®cant increase in the length of DNA loops (Micheli et al, 1993). This general rearrangement of the higher order structure of chromatin re¯ects a reduction of the number of associations of MAR/SAR to the sca old and matrix.…”
Section: Dna Loop Domains and Organization Of Replicationmentioning
confidence: 99%